CRIMINOLOGICAL AND VICTIMOLOGICAL DETERMINANTS OF PROSTITUTION – PROPOSALS DE LEGE FERENDA - Pavlović, Zoran; Petković, Nikola (Glasnik Advokatske komore Vojvodine, 2024)
Prostitution is a complex social phenomenon that often integrates criminological and victimological perspectives. Juxtaposed with the idea of sexual freedom, the right to dispose of one's own body, and the obligation to protect morality, prostitution finds different social responses. Discussing the concept of authentic and apparent prostitution, the authors will try to bring a conceptual analysis, as well as a draft of a new legislative model for regulating the subject area. By integrating the tendencies of socio-psychological and health care, as well as minimizing stigmatization and discrimination, a stratified model of social response will be presented below, which ultimately does not give up on the protection of morality as a social and legal category, as a vital social component.
Keywords: Prostitution, morality, social protection, sanctioning